Peripheral T-Cell Lymphomas Involving the Central Nervous System: A Report From the Czech Lymphoma Study Group Registry - Mocikova, Heidi; Pytlík, Robert; Benesova, Katerina; Janikova, Andrea; Duras, Juraj; Sykorova, Alice; Steinerova, Katerina; Prochazka, Vit; Campr, Vit; Belada, David; Trneny, Marek (Frontiers in Oncology, 2022)
Introduction. We analyzed the incidence, risk factors of central nervous system (CNS) relapse and outcome of CNS involvement in patients with peripheral T-cell lymphomas (PTCL) from the Czech Lymphoma Study Group Registry NiHiL (Clinical Trial gov. NCT03199066). Materials and Methods. Out of 1040 patients with PTCL we identified 29 patients (2.79%) with CNS involvement: 2 patients with primary CNS T cell lymphoma, 11 patients with CNS and systemic disease at diagnosis and 16 patients (1.54%) at CNS relapse. Progression-free survival (PFS) was defined as the time interval from diagnosis to progression or death. PFS-2 was defined as the interval from the date of a new relapse until the next relapse. Results. Patients with testicular involvement received intrathecal prophylaxis with methotrexate. High dose methotrexate based treatment was administered in 44.8% of patients with CNS disease. Median follow-up was 71.3 months. The difference between median PFS of 1027 patients without initial CNS disease (32.6 months) and 11 patients with initial CNS and systemic disease (4.8 months) was significant (p=0.04). The difference between median PFS2 in CNS relapses (10.1 months) and 493 relapses outside of CNS (9.1 months) was not significant (p=0.6). Risk factors for CNS relapses included: involvement of more than one extranodal site (p=0.008), soft tissue involvement (p=0.003), testicular involvement (p=0.046) and presence of B symptoms (p=0.035). The difference between median OS of 1027 patients without initial CNS disease (46.0 months) and 11 patients with initial CNS and systemic disease (18.2 months) was significant (p=0.02). Median OS2 in CNS relapses was 11.8 months and in relapses outside of CNS 21.3 months. CNS involvement was not associated with a significantly worse OS compared to relapsed/refractory patients without CNS involvement (p=0.1). Conclusions. The incidence of CNS disease at the time of diagnosis and at relapse in PTCL is low and usually associated with other systemic involvement. The prognosis of PTCL with initial CNS involvement is significantly worse when compared to patients without CNS disease at diagnosis. The outcome of CNS relapse is comparable with relapsed PTCL outside of CNS. The optimal treatment is not defined yet.